Stepwise increase of fidaxomicin in an engineered heterologous host Streptomyces albus through multi-level metabolic engineering - Huang Xie; Yi-Ting Su; Qing-Ting Bu; Yue-Ping Li; Qing-Wei Zhao; Yi-Ling Du; Yong-Quan Li (Synthetic and Systems Biotechnology)
The anti-Clostridium difficile infection (CDI) drug fidaxomicin is a natural polyketide metabolite mainly produced by Micromonosporaceae, such as Actinoplanes deccanensis, Dactylosporangium aurantiacum, and Micromonospora echinospora. In the present study, we employed a stepwise strategy by combining heterologous expression, chassis construction, promoter engineering, activator and transporters overexpression, and optimization of fermentation media for high-level production of fidaxomicin. The maximum yield of 384 mg/L fidaxomicin was achieved with engineered Streptomyces albus D7-VHb in 5 L-tank bioreactor, and it was approximately 15-fold higher than the native strain Actinoplanes deccanensis YP-1 with higher strain stability and growth rate. This study developed an enhanced chassis strain, and for the first time, achieved the heterologous synthesis of fidaxomicin through a combinatorial metabolic engineering strategy.